Parental stress and paediatric acquired brain injury. (6th December 2018) - Labrell, Florence; Câmara-Costa, Hugo; Dufour, Christelle; Grill, Jacques; Dellatolas, Georges; Chevignard, Mathilde
ABSTRACT: Objective : Studies on parental stress following childhood acquired brain injury (ABI-including brain tumours (BT) and other brain injuries) are scarce. The aim of this study was to assess maternal stress in a sample of children and adolescents diagnosed with severe paediatric ABI. Methods : Seventy-eight French-speaking mothers of 37 with BT and 41 with other ABIs completed the Paediatric Inventory for Parents (PIP), the State-Trait Anxiety Inventory (STAI) and the Family Assessment Device (FAD) at a mean time since diagnosis of 1.5 years. Results : The PIP correlated significantly with the STAI and the FAD. Socio-demographic factors, such as the age of mother and child, and the mother's educational level, were correlated with both maternal stress and anxiety. Maternal stress scores were comparable between groups. Emotional functioning was the most markedly affected domain, followed by parental role. Conclusions : Emotional stress as assessed by the PIP in mothers of children with ABI is significant and should motivate specific psychosocial interventions.